Multiple positive solutions of Strum-Liouville equations with singularities - Zenggui Wang; Lishan Liu; Yonghong Wu (Discrete Dynamics in Nature and Society)
The existence of multiple positive solutions for Strum-Liouville boundary value problems with singularities is investigated. By applying a fixed point theorem of cone map, some existence and multiplicity results of positive solutions are derived. Our results improve and generalize those in some well-known results.